2022
DOI: 10.1186/s12871-022-01681-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and risk factors for delayed-onset postoperative respiratory failure: a multi-center case-control study by the University of California Critical Care Research Collaborative (UC3RC)

Abstract: Background Few interventions are known to reduce the incidence of respiratory failure that occurs following elective surgery (postoperative respiratory failure; PRF). We previously reported risk factors associated with PRF that occurs within the first 5 days after elective surgery (early PRF; E-PRF); however, PRF that occurs six or more days after elective surgery (late PRF; L-PRF) likely represents a different entity. We hypothesized that L-PRF would be associated with worse outcomes and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…All these factors can impair the function of respiratory muscles, leading to a decrease in functional residual capacity and vital capacity. 29 In this study, the functional capacity of the patients preoperatively was assessed by 6MWT and the results showed that there was no significant difference in all the related indicators including walk distance, Borg-score, MAP, HR, and SpO2 between the two groups. However, SpO2 in the VIS group was significantly higher than that in the control group on the 3rd and 5th postoperative day, indicating that postoperative hypoxemia was reduced by using VIS.…”
Section: Discussionmentioning
confidence: 72%
“…All these factors can impair the function of respiratory muscles, leading to a decrease in functional residual capacity and vital capacity. 29 In this study, the functional capacity of the patients preoperatively was assessed by 6MWT and the results showed that there was no significant difference in all the related indicators including walk distance, Borg-score, MAP, HR, and SpO2 between the two groups. However, SpO2 in the VIS group was significantly higher than that in the control group on the 3rd and 5th postoperative day, indicating that postoperative hypoxemia was reduced by using VIS.…”
Section: Discussionmentioning
confidence: 72%
“…[ 25 26 27 28 ] Clinical frailty ≥4, as assessed according to the Clinical Frailty Scale, is considered the threshold representative of frailty, which has a robust impact on the incidence of postoperative severe complications as studied on elderly patients with colorectal surgery. [ 11 15 27 28 29 30 ] Studies using the most commonly applied index in surgical cohorts across multiple surgical specialties, that is, the modified Frailty Index (mFI), showed that frailty is associated with a higher rate of all-cause complications and mortality. [ 16 ] mFI is easy to calculate and uses characteristics extracted from the patient’s history and examination.…”
Section: The Geriatric Patient Population—the Fastest Growing Group I...mentioning
confidence: 99%